Implementasi Prinsip-Prinsip Ekonomi Islam dalam Konteks Ekonomi Indonesia - Rayyahun, Annisa; Amiruddin; Rifqi (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
This study examines the system and principles of Islamic economics from both a theoretical perspective and its contemporary implementation in Indonesia. Using a literature review method and a descriptive-analytical approach, the research aims to identify and analyze the fundamental principles of Islamic economics, such as tauhid, justice, khilafah, and al-Mas’uliyah, as well as evaluate their application in the context of modern economics in Indonesia. Through a review of relevant literature sources, this study finds that although Islamic economics holds significant potential to create a just and sustainable system, its implementation in Indonesia faces various challenges, such as social inequality, unsustainable resource management, and lack of transparency in business practices. Therefore, efforts are needed to improve the understanding and implementation of Islamic economic principles to create a more inclusive and just economic system.